Response of wheat to tillage and row spacing in maizewheat cropping system in semi-arid region of Pakistan - Shahid, Ibni Zamir; Ahma, Azraf-Ul-Haq; Rashad Javeed, H. M. (Agrociencia Uruguay, 2012)
A field study was conducted to determine the effect of tillage and row spacing on growth and yield of wheat (Triticum aestivum L.) at Agronomic Research Area, University of Agriculture, Faisalabad, Pakistan during winter 2005-2006 and 2006-07. The treatments comprised two tillage practices viz. zero tillage and conventional tillage and four row spacings i.e. 15, 20, 25 and 30 cm. The experimental results revealed that zero tillage signifi cantly enhanced the plant height, tillers m-2, spike length, 1000 kernel weight and yield and yield components of wheat plants as compared to conventional tillage. Sowing of wheat in 15 cm apart rows resulted in signifi cantly higher grain yield due to higher number of tillers. So, zero tillage and narrow row spacing (15 cm) proved to be involved in higher wheat yield for the wheat-maize cropping system in semi-arid region of Pakistan.